Rancangan Sistem Informasi Kepatuhan Minum Obat Malaria dalam Menunjang Penerapan Sistem Kepatuhan Minum Obat pada Pasien Malaria Tertiana - Diliani Diliani; Budiman Budiman; Lina Safarina; Nurharlinah Nurharlinah; Suharjiman Suharjiman (Journal of Telenursing (JOTING), 2023)
This study aims to explore the experiences of malaria patients regarding medication adherence and design a model for medication adherence in malaria patients. This research method is qualitative research with an action research approach. The study results produced a design for SIPENGUAT (Medicine Taking Reminder Information System). The conclusion is that the client's experience regarding compliance with taking medication was that the client did not comply/completely consume Primaquin medication for 14 days because he forgot, was healthy, and took the medicine for a long time. This research produced a design for an information system for adherence to taking malaria medication, namely SIPENGUAT. Keywords: Compliance, Malaria, Design